PENGARUH ECONOMIC VALUE ADDED DAN PROFITABILITAS TERHADAP RETURN SAHAM PADA PERUSAHAAN SUBSEKTOR PERDAGANGAN RITEL YANG TERDAFTAR DI BEI PERIODE 2013-2017 - Hendayana, Yayan; -, Nurlina (Fakultas Ekonomi dan Bisnis Universitas Islam As-Syafi'iyah, 2020)
This study aims to determine the effect of profitability as measured by Economic Value Added, Return on Assets, and Return on Equity on Stock Returns in retail trading sub-sector companies on the Indonesia Stock Exchange 2013-2017 period. 10 companies have been selected as samples based on predetermined criteria. The approach taken in this research is associative. The data collection technique in this research is the documentation technique. Hypothesis testing uses panel data regression analysis using the Eviews 9 program. Based on the results of the regression coefficient and t-test it shows that partially Economic Value Added and Return on Equity have a significant positive effect on stock returns, while Return on Assets has a significant negative effect on stock returns.